(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The process of improving naturally occurring groundwater supplies by means of artificial conveyances such as infiltration basins, trenches, dams, or injection wells is known as groundwater recharge. One particular kind of recharge that increases groundwater resources and recovers water for later use is called aquifer storage and recovery, or ASR. Water moves through the saturated zone in a complicated process that might be facilitated by hydraulic or gravity forces. Large errors in recharge estimates and unmetered groundwater consumption are common in groundwater modeling studies, and these can have an influence on ecosystems that depend on groundwater, extractive industries, and sustainable yields. In order to artificially recharge aquifers, surface water is placed in basins or furrows, where it seeps into the ground and descends to replenish it. Permeable surface soils are necessary for this technique, which is being employed more and more for subterranean storage. Test basins and field research are required to forecast system functionality. The quality of the water is assessed, with a focus on geochemical reactions in the aquifer and fouling layers on basin bottoms. Periodically pump recharge wells to backwash clogging layers.